An Integrated Model of Cumulative Growth: Empirical Evidence for Nine OECD Countries, 1960-1990 - Paolo Pini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1994)
This paper is an empirical analysis of the interaction between the dynamics of demand, productivity and employment in nine industrial countries, viz. The United States, Canada, Japan, West Germany, France, Italy; the United Kingdom, the Netherlands, and Belgium, from 1960-1990. Its theoretical framework derives from the Kaldorian approach to cumulative growth in both its external and internal causation versions. The model we adopt is of an integrated kind, in which foreign demand is determined endogenously and domestic demand is divided up into its various component parts: exogenous for the public sector and endogenous for the private. More specifically, this is carried out by describing the way the dynamics of private cosumption and private investments depend on economic variables located in the spheres of distribuction and of technology, so that we can consider the operations of income compensation effects induced by technological change – via changes in income and its social distribution – as well as price compensation effects – the higher competitiveness of national products in foreign markets – mediated through the dynamics of exports.
Keywords: 330